y+7(4)=11

Simple and best practice solution for y+7(4)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+7(4)=11 equation:


y+7(4)=11

We simplify the equation to the form, which is simple to understand
y+7(4)=11

Reorder the terms in parentheses
y+(+28)=11

Remove unnecessary parentheses
+y+28=+11

We move all terms containing y to the left and all other terms to the right.
+1y=+11-28

We simplify left and right side of the equation.
+1y=-17

We divide both sides of the equation by 1 to get y.
y=-17

See similar equations:

| 4x+-5=2(2x+1) | | 8x+10x=44 | | 4(b-1)+2(3+b)=9 | | 0=8y-56 | | 5x+51=x+19 | | 5+9z=10+9z | | x+100+45=180 | | 144t^2+1/t^2+24 | | 2x-(56)=5 | | 144t^2+1/t^2 | | -12x-3=27-9x | | (12-15n)/(5n^2+6n-8) | | k/3=-17 | | c-68=-121 | | ((x+7)/(x+3))=((x-2)/(x+1))+1 | | 6x-3=3-6x | | x/7-2=9/14 | | x-3=21.6 | | 4*2+1= | | 2x+16=y | | -18+x=10 | | 6+5y-1=8y+6-2y | | 2/-5*u=23 | | 550/1+4p=-9+2p | | 5a+7=4a-9 | | 2(y+2)-4=12 | | ((y-5)/(y-6))-1=((y-3)/(y-7)) | | 1/2b6=87 | | 4(4x-3)-6x=12-12-2x | | =p+p^2 | | 45y^2-60xy+20x^2=0 | | 3x-8=3x-5 |

Equations solver categories